Estimativas satelitárias de precipitação sobre o bioma cerrado: possibilidades e perspectivas - Farias, Sylvia Elena de Marques (2016)
The Brazilian savanna is the second largest biome, covering an approximate area of 21% of the national territory. Among other factors, the rainfall favored the activities of agribusiness and hydro-dependent activities of the climate pattern of rainfall. However, the biome is complex climatologically and rainfall network is sparse or poorly distributed. In this sense, this study sought to evaluate the precipitation estimates of the Savanna. The main results of this thesis are: a) by the need to assess the rainfall pattern on the Savanna it was found that the rains are caused due to phenomena of weather and climate that operate seasonally, featuring the region by dry winters, from May to August, and rainy summers, from September to April. A deficit above -5,0 mm.mes-1 is observed between May and June, while the excess water, the rainy season can reach 240,0 mm.mes-1; b) given the complexity rainfall observed in the biome, statistical tests showed that version 7 algorithm was more accurate to estimate precipitation. As for the regions of the state inserted in the biome, Goiás presented the highest value as the Pearson correlation, 0,99. Estimates between area and pixel showed that the satellite estimates are consistent with the observations. Considering the ability of estimates of the annual and seasonal pattern, the precipitation anomalies reproduce the variability of dry and wet periods. The estimate for the year 2009, under the influence of the beginning of a moderate El Nino, played a rainy year throughout the Savanna. Conversely, 2007, characterized by end of an El Nino low intensity, reproduced a dry year; c) Analysis of Main Components (ACP) were characterized by the three most significant factors explaining 97,5% of the total variance of monthly precipitation data both for Brazil and for the Savanna. The CP1 varies linearly indicating that it explains both the Savanna as to Brazil the annual variation in rainfall. The CP2 brand significantly seasonality between Brazil and the Savanna. The CP3 varies significantly between characteristic months due to seasonality. The results suggest that the satellite rainfall estimates, version (3B43), are accurate on a complex and extensive biome as the Savanna.